Association mapping unravels the genetics controlling seedling drought stress tolerance in winter wheat - Schierenbeck, Matías; Alqudah, Ahmad M.; Thabet, Samar G.; Lohwasser, Ulrike; Simón, María Rosa; Börner, Andreas (Frontiers in Plant Science, 2023)
Drought or water deficiency is a major yield-limiting factor causing losses of up to 80% of wheat (Triticum aestivum L.) grain yield. The present work aimed to identify quantitative trait nucleotides (QTNs)/ candidate genes influencing drought tolerance-related traits at the seedling stage in 261 accessions of a diverse winter wheat panel. Seeds from three consecutive years were exposed to drought stress induced by 12% polyethylene glycol (PEG 6000) and a control treatment (distilled water). Drought stress induced by PEG reduced shoot length (SL) (-36.3%) and root length (RL) (-11.3%) compared with control treatments, while the coleoptile length (CL) was increased under drought conditions by 11% suggesting that it might be considered as an indicator of stress-tolerant. The association analysis was performed using 17,093 polymorphic SNPs in the FARM-CPU model. Interestingly, we revealed 70 stable QTN across 17 chromosomes in at least two environments. Furthermore, eight multi-traits associated QTNs were found on chromosomes 1B, 2A (2), 2B, 2D, 4B, 7A, and 7B and located nearby or inside candidate genes within the linkage disequilibrium (LD) interval. For instance, the QTN on chromosome 2D is located inside the gene TraesCS2D02G133900 that controls the variation of CL_S and SL_C. The allelic variation at the candidate genes showed significant influence on the associated traits, demonstrating their role in controlling the natural variation of multi-traits of drought stress tolerance. The gene expression of these candidate genes under different stress conditions validates their biological role in stress tolerance. QTNs obtained through this study could then be used for selection in wheat breeding programs and be a molecular source of drought tolerance.